Histological and transcriptional characterization of the pancreatic acinar tissue in type 1 diabetes - Louise Granlund; Anders Hedin; Miriam Wahlhütter; Peter Seiron; Olle Korsgren; Oskar Skog; Marcus Lundberg (BMJ Open Diabetes Research & Care)
Introduction Despite a reduced function and volume of the exocrine pancreas in type 1 diabetes, the acinar cells remain understudied in type 1 diabetes research. The hypothesis of this study is that the acinar tissue is altered in subjects with type 1 diabetes compared with subjects without diabetes.Research design and methods The cell density, expression of digestive enzymes, and transcriptome of acinar tissue at varying distances from islets were analyzed using histology, immunostaining, and AmpliSeq RNA sequencing of laser capture microdissected tissue. Pancreases examined were from organ donors with or without type 1 diabetes.Results We demonstrate preserved acinar nuclei density and find no support of acinar atrophy in type 1 diabetes. Staining for digestive enzymes (amylase, lipase, and trypsin) demonstrated an evenly distributed expression in the exocrine parenchyma; although occasional amylase-negative regions appeared in tissue that had been formalin-fixed and paraffin-embedded, this phenomenon was not evident in frozen tissue. Gene set enrichment analysis of whole transcriptome data identified transcriptional alterations in type 1 diabetes that were present in the acinar tissue independent of the distance from islets. Among these, the two most enriched gene sets were Myc Targets V2 and Estrogen Response Early.Conclusion Taken together, these new data emphasize the involvement of the entire pancreas in type 1 diabetes pathology. The alteration of the gene sets Myc Targets V2 and Estrogen Response Early is a possible link to the increased incidence of pancreatic cancer in type 1 diabetes.